A novel double Ag@AgCl/Cu@Cu2O plasmonic nanostructure: Experimental design and LC-Mass detection of tetracycline degradation intermediates. (6th January 2021) - Derikvandi, Hadis; Vosough, Maryam; Nezamzadeh-Ejhieh, Alireza
Abstract: Here a novel sunlight-driven double-plasmonic Ag @ AgCl/Cu @ Cu2 O nanophotocatalyst was constructed via photochemical-conversion and photoreduction methods for the first time. The as-prepared Ag @ AgCl/Cu @ Cu2 O was characterized by several characterizations techniques. The Scherrer equation showed the crystallite sizes of 37, 25, and 40 nm for the as-prepared Ag @ AgCl, Cu @ Cu2 O and Ag @ AgCl/Cu @ Cu2 O catalysts, while their band gap energies were 3.36, 2.51, and 3.04 eV (DRS results), respectively. TC (tetracycline) served as a probe to study its photocatalytic activity under sunlight. It was found that the as-prepared nanophotocatalyst with suitable Ag @ AgCl and Cu @ Cu2 O content not only demonstrated superior photocatalytic activity to both Ag @ AgCl and Cu @ Cu2 O plasmonic nanoparticles, but also had remarkable photostability due to the presence of two simultaneous surface plasmon resonance (SPR) in metallic Ag and Cu NPs and the hetero-junction structure formed at the interface between Ag @ AgCl and Cu @ Cu2 O. The main active species were detected through a trapping experiment which confirmed that O2 − and OH were the main active species in the photocatalytic system. Central composite design (CCD) was used for the modeling and optimization of the photodegradation process. The possible photocatalytic degradation pathway of TC was proposed based on the identified intermediates. The photodegradation rate constant of TC was about 0.043 min −1 (t1/2 = 0.910 min) (in the range of 5–60 min). The optimum RSM run had the conditions the TC concentration of 2.0 (mg/L), Ag @ AgCl/Cu @ Cu2 O dosage of 0.53 (g/L), irradiation time 18 (min), and pH value of 6.5. Graphical abstract: Image 1 Highlights: Novel sunlight-driven double plasmonic photocatalysts, Ag @ AgCl/Cu @ Cu2 O. Superior photocatalytic activity of Ag @ AgCl/Cu @ Cu2 O compared to Ag @ AgCl and Cu @ Cu2 O. Red shifts in band gaps of the coupled semiconductors compared the single systems. Prompted activities due to the strong SPR effect of Ag and Cu NPs and heterojunction. The O 2− and OH as the main active species in the TC photodegradation.